Aprovechamiento de biomasa lignocelulósica: Eichhornia crassipes (Lechuguines) para la obtención de bioplástico - Zambrano Saltos, Andy David (2022)
In order to mitigate the phenomenon of eutrophication in freshwater bodies and give added value to the aquatic species Eichhornia Crassipes (Lechuguines), it was treated to be used in the field of biorefinery, as an alternative to conventional plastics. The objective of this research is to take advantage of the lignocellulosic biomass of lechuguines to obtain bioplastic. The biomass of the research comes from the Poza Honda dam, where the lignocellulosic content was synthesized to obtain the cellulose. The research methodology consists of three processes: extraction of cellulose, starch and obtaining bioplastic, applying alkaline hydrolysis in the extraction of cellulose and sodium hypochlorite as a bleaching agent, the wet method was applied for sedimentation and obtaining starch. In the characterization of the product obtained, the humidity was 19%, the volatile content 7.13%, the water absorption was increasing 31.05%, the degree of biodegradability 66.33%. In conclusion, the biomass of Eichhornia Crassipes is a significant source for the production of bioplastic, the biodegradability of the biofilms obtained is very satisfactory, being within the range of international standards ASTM D-6400